Dual kinetic and structural role for the surface in guiding SAS-6 self-assembly to direct centriole architecture [data]: coarse-grained molecular dynamics simulation data - Buhr, Svenja de; Gräter, Frauke (Universität, 2021)
This dataset contains input structures and parameters for coarse-grained molecular dynamics simulation of SAS-6 protein oligomers as well as post-p...